Encyonema capixabense sp. nov. (Cymbellales, Bacillariophyceae): a widespread diatom in Brazilian rivers first described from the Rio Doce Basin (southeastern Brazil) - Marquardt, Gisele C.; Morais, Krysna S.; Costa, Beatriz C.; Fernandes, Valéria O.; Zorzal-Almeida, Stéfano (Phytotaxa, 2025)
A new diatom species, Encyonema capixabense sp. nov., is described from periphytic material collected during a monitoring survey of the Rio Doce, southeastern Brazil. Its morphology is documented using light and scanning electron microscopy. This taxon is characterized by i) semi-lanceolate valves, ii) a slightly tumid ventral margin with convergent striae, and iii) valve ends deflected toward the ventral side. The new species is compared with morphologically similar taxa within the genus based on the literature. We confirmed that the new species was previously recorded under different names in several Brazilian studies and exhibits a broad occurrence in rivers. In this study, it dominates periphyton communities in mesotrophic lotic environments. Our results emphasize the need for increasing efforts to better understand the flora of poorly studied regions.